1980
DOI: 10.1126/science.6775372
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Metabolism: A Potential Therapeutic Target in Trypanosomes

Abstract: alpha-Difluoromethylornithine (RMI 71,782), a specific irreversible inhibitor of the first step in polyamine biosynthesis, that is, the formation of putrescine from ornithine by ornithine decarboxylase, cures mice infected with a virulent, rodent-passaged strain of Trypanosoma brucei brucei. This parasite is closely related to the trypanosomes that cause human sleeping sickness. The drug, which is remarkably nontoxic, was effective when administered in drinking water or by intubation. The ability of the compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
184
0
4

Year Published

1983
1983
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(188 citation statements)
references
References 18 publications
0
184
0
4
Order By: Relevance
“…An analysis of the period showed that cases of HAT occurred significantly more often in settings with political turmoil and internationalized civil war, with a 10-year interval between onset of conflict and peak prevalence (132). By the 1990s, epidemic disease had returned to central Africa (113,130,133,134). By 1995, the reported annual number of cases of gambiense HAT had reached levels not seen for half a century, which was particularly alarming because only a small fraction of the areas at risk were under surveillance, and the true magnitude of the epidemic was unknown.…”
Section: Gambiense Human African Trypanosomiasismentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the period showed that cases of HAT occurred significantly more often in settings with political turmoil and internationalized civil war, with a 10-year interval between onset of conflict and peak prevalence (132). By the 1990s, epidemic disease had returned to central Africa (113,130,133,134). By 1995, the reported annual number of cases of gambiense HAT had reached levels not seen for half a century, which was particularly alarming because only a small fraction of the areas at risk were under surveillance, and the true magnitude of the epidemic was unknown.…”
Section: Gambiense Human African Trypanosomiasismentioning
confidence: 99%
“…Surveillance for gambiense HAT decreased and was curtailed in many areas as public health authorities in the newly independent countries turned their attention and resources to other priorities. In addition, conflicts and insecurity constrained disease control interventions (130,131). An analysis of the period showed that cases of HAT occurred significantly more often in settings with political turmoil and internationalized civil war, with a 10-year interval between onset of conflict and peak prevalence (132).…”
Section: Gambiense Human African Trypanosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…Son utilisation en thérapeutique est récente et fait suite à l'identification des mécanismes moléculaires spécifiques de processus pathologiques [29][30][31]. Apparaît en filigrane le souhait d'éviter de léser les tissus sains ou encore, en restant dans la métaphore guerrière, d'éviter les dégâts collatéraux des médicaments.…”
Section: Thérapies Ciblées Beaucoup De Marketingunclassified
“…Polyamines play an important role in the proliferation and differentiation of pathogenic protozoa. 43 These quaternary ammonium compounds (putrescine, spermidine, and spermine) are important in nucleic acid and protein synthesis. The ornithine decarboxylase (ODC) inhibitor D-Lalpha difluoromethyl ornithine (DFMO) has been effective in the treatment of African sleeping sickness.…”
Section: Introductionmentioning
confidence: 99%